The power of self-advocacy for gifted learners teaching the 4 essential steps to success - Douglas, Deb 1950- (Free Spirit Publishing Inc., 2018)
"Book for educators on teaching self-advocacy skills to gifted learners in four steps: 1) understand their rights and responsibilities, 2) develop their learner profiles, 3) investigate options and opportunities, 4) connect with advocates. Included are instructions for conducting a day-long self-advocacy workshop with gifted students. Digital content included."--Provided by publisher.